(3CSeGA GdTYQGA hGdYdeGA GdPjf hbY PcQge aj TQM GdQVi Ydi GdcGajgs - (3YHO GdbGOQ Hf YeQ GdHZOGOj,J (B1093 (3g` s ((3eMeO YHO GdbGOQ Hf YeQ GdHZOGOi s)
(3ChdgG (B:s
(3CeG HYO agPg agQSJ GSeGA GdTYQGA GdPjf GSJTgO GdYdGeg GdQVi HTYQge ai TQM GdcGajI hCSeGA HYV GdYdeGA hbY PcQge s
(3BNQgG (B:s
(3jRjd Hg GdYdGA hjeJgf bQH GdGbQHjf hGdebUi GHdi eG PGb aJCHjg edP OhGA hfU Uhdjg JeJ GdCHjGJ s
(3Vef eLehY , JQJjHgG (B: (3ef U (B138 - (3U(B145s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B41 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B295s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B286 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe LRA (B2/ 1 - (3U (B14 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs